Body composition and heart rate variability to achieve dry weight and tolerance - Nalesso, F; Ferrario, M; Moissl, U; Brendolan, A; Zanella, M; Cruz, D N; Basso, F; Floris, M; Clementi, A; Garzotto, F; Tetta, C; Signorini, M G; et al. (Contributions to nephrology, 2011)
Autonomic dysfunction in patients with end- stage renal disease is associated with poor prognosis. Heart rate variability (HRV), determined by the standard deviation of the normal R- R interval, has been reported to be a useful evaluation of cardiac autonomic modulation. The relationship between HRV and hydration status (HS) can be analyzed by whole body bioimpedance spectroscopy. This allows a classification of patients according the combination of HS with predialysis systolic blood pressure. Differences in HRV can be studied in patients with high over hydration, but normal or low blood pressure, with respect to fluid-overloaded/hypertensive patients and normohydrated/normotensive patients. In conclusion, the assessment of the autonomic nervous system response to the hemodialysis treatment in end- stage renal disease patients, classified according to a reliable and quantitative measurement of their fluid overload, could permit better management of both arterial blood pressure and HS.